2011
DOI: 10.2146/ajhp100321
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of a heparin correlation value for activated partial thromboplastin time in heparin nomograms

Abstract: PURPOSE. Use of nomograms based on the "heparin correlation value" (HCV)-a value that corresponds to measured activated partial thromboplastin time (aPTT) and that removes the need to revise nomograms in response to a change in the aPTT reagent or coagulometer used-was evaluated as an alternative to traditional aPTT-based anticoagulation nomograms. SUMMARY. Data were collected on patients receiving heparin therapy for selected indications (thrombotic disorders, cardiac conditions, and acute coronary syndromes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To our knowledge, this is the second largest of only 4 previous studies which directly compared aPTT and anti-Xa nomograms for monitoring UFH. 8 10,12 Rosborough evaluated 268 patients who received a single treatment protocol based on deep vein thrombosis (DVT) treatment and showed that despite a modest increase in cost, patients in the anti-Xa group required fewer monitoring tests and dose changes compared to the aPTT. 8 Fruge and Lee studied 141 patients who received a single protocol for all indications, although dosing differed slightly between the aPTT and anti-Xa nomograms.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the second largest of only 4 previous studies which directly compared aPTT and anti-Xa nomograms for monitoring UFH. 8 10,12 Rosborough evaluated 268 patients who received a single treatment protocol based on deep vein thrombosis (DVT) treatment and showed that despite a modest increase in cost, patients in the anti-Xa group required fewer monitoring tests and dose changes compared to the aPTT. 8 Fruge and Lee studied 141 patients who received a single protocol for all indications, although dosing differed slightly between the aPTT and anti-Xa nomograms.…”
Section: Discussionmentioning
confidence: 99%
“…A therapeutic aPTT range is determined by plotting on a graph simultaneous aPTT and antifactor Xa values from patients receiving heparin, and from the lines of best fit, finding the aPTT values that correspond to 0.3 and 0.7 unit/ml, respectively. With the large degree of variability already known, and the enhanced availability of antifactor Xa automation, some investigators sought to explore if the use of antifactor Xa levels directly for patient care was more feasible than their use in establishing institution‐specific aPTT goal ranges (Table ) …”
Section: Clinical Trials Comparing Activated Partial Thromboplastin Tmentioning
confidence: 99%
“…A prospective, observational, cohort study evaluated the use of a heparin correlation value, in which the antifactor Xa concentrations were correlated with the aPTT, then the measured aPTT was correlated back to antifactor Xa levels; use of this value may help to account for disadvantages of both monitoring methods. Only the aPTT (and not the antifactor Xa level) is measured with this method, but the result is recalculated as a heparin correlation value.…”
Section: Clinical Trials Comparing Activated Partial Thromboplastin Tmentioning
confidence: 99%
See 2 more Smart Citations